2022
DOI: 10.1093/cid/ciac913
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Culture-Based Versus Empirical Antibiotic Prophylaxis to Prevent Infectious Complications in Men Undergoing Transrectal Prostate Biopsy: A Randomized, Nonblinded Multicenter Trial

Abstract: Background An increase of infections after transrectal prostate biopsy (PB), related to an increasing number of patients with ciprofloxacin-resistant rectal flora, necessitates the exploration of alternatives for the traditionally standard used empirical prophylaxis with ciprofloxacin. We compared infectious complication rates after transrectal PB using empirical ciprofloxacin prophylaxis versus culture-based prophylaxis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…54 Rectal culture should be performed to avoid infective complications following the procedure and a targeted prophylactic treatment should be started. In the study of Tops et al 61 patients were divided in a control group (who took ciprofloxacin empirically) and in a treatment group (antibiotic choice was based on the preoperative rectal culture and antibiogram). Patients who underwent a rectal culture sample collection showed a statistically significant reduction in infectious complication rates when compared to empirically treated patients [OR 0.52, 95% CI 0.27-0.99].…”
Section: Prostate Biopsymentioning
confidence: 99%
“…54 Rectal culture should be performed to avoid infective complications following the procedure and a targeted prophylactic treatment should be started. In the study of Tops et al 61 patients were divided in a control group (who took ciprofloxacin empirically) and in a treatment group (antibiotic choice was based on the preoperative rectal culture and antibiogram). Patients who underwent a rectal culture sample collection showed a statistically significant reduction in infectious complication rates when compared to empirically treated patients [OR 0.52, 95% CI 0.27-0.99].…”
Section: Prostate Biopsymentioning
confidence: 99%
“…Tops et al [52 ▪ ] conducted a large, sufficiently powered nonblinded RCT (n = 1288) in which patients undergoing TRPBs self-sampled a rectal swab (7–60days prior to procedure) and were then randomised to receive empirical prophylaxis (oral ciprofloxacin) as a control; or culture-based prophylaxis as the intervention. Infection rates as 7 days postbiopsy (primary outcome) were 4.3% for empirical therapy and 2.5% for culture-based therapy (Reduction: −1.8%; 95% CI, −0.004 to 0.040; P = 0.08).…”
Section: Urological Surgerymentioning
confidence: 99%
“…Five studies were identified [26,49,50,51 ▪▪ ,52 ▪ ] of which only two had greater than 500 participants [51 ▪▪ ,52 ▪ ].…”
Section: Urological Surgerymentioning
confidence: 99%
“…The application of MRI‐TBx might be restricted by some limitations (eg its high cost, complex operation, and limited availability). Although the combined biopsy added with MRI‐TBx improved the detection rate of PCa, complications (eg infection, pain, and bleeding) caused by added biopsy cores also increases 16,17 …”
mentioning
confidence: 99%
“…Although the combined biopsy added with MRI-TBx improved the detection rate of PCa, complications (eg infection, pain, and bleeding) caused by added biopsy cores also increases. 16,17 The aim of this study was to assess the diagnostic value of MRI-TBx compared to TRUS-SBx and combined biopsy and to further determine the effectiveness and accuracy of MRI-TBx based on PI-RADS v2.1 in TZ and PZ, respectively.…”
mentioning
confidence: 99%